Prognostic Value of Circular RNA ciRS-7 in Various Cancers: A PRISMA-Compliant Meta-Analysis. (23rd January 2020) - Tian, Guangwei; Li, Guang; Guan, Lin; Wang, Zihui; Li, Nan
Abstract : Background . Circular RNAs (circRNAs) have been shown to be involved in tumorigenesis. As a member of circRNAs, ciRS-7 is thought to be a negative prognostic indicator in multiple types of cancer. The present study aimed to comprehensively explore the value of ciRS-7 in tumor malignancy. Materials and Methods . A systematic review of PubMed, Web of Science, and the Cochrane library was carried out to examine the related studies. The pooled odds ratios (ORs) and hazard ratios (HRs) with 95% confidence intervals (95% CIs) were calculated from the available publications by STATA 12.0. Subgroup analysis, publication bias, sensitivity analysis, and meta-regression were conducted. Results . This meta-analysis included 1, 714 patients from 13 cohorts. The results suggested that high ciRS-7 expression was significantly associated with overall survival (OS) (HR = 2.17, 95% CI = 1.50–3.15, P < 0.001 ) in various cancers. Stratified analyses indicated that elevated levels of ciRS-7 appeared to be a powerful prognostic biomarker for patients with non-small-cell lung cancer (NSCLC) (HR: 2.50, 95% CI: 1.07–6.07, P = 0.035 ), colorectal cancer (CRC) (HR: 1.95, 95% CI: 1.34–2.84, P < 0.001 ), and gastric cancer (GC) (HR: 2.32, 95% CI: 1.48–3.64, P < 0.001 ). A similar effect was also observed in subgroup of sample size, analysis method, and cutoff value, except for ethnicity. The increased ciRS-7 expression was associated with a higher tumor stage (OR = 2.30, 95% CI: 1.69–3.13, P < 0.001 ). Conclusions . High expression of ciRS-7 has a significant correlation with the high stage in various cancers, and ciRS-7 is intimately associated with an adverse OS in numerous cancers. Thus, ciRS-7 may act as a potential biomarker for the development of malignancies.